Capacitación científica y actividades de la red. Africa - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Detailed information on the activities of the CIAT breeding program and African regional and national programs is presented, with special emphasis on the Great Lakes Regional Project in Central Africa. The main activities carried out in 1985 in the areas of training, var. development and introduction, cultural and chemical control of diseases and pests, nutritional studies (cooking time and protein content), on-farm research, bean consumption preference surveys, and on-farm var. trials are summarized and major results are given. Future plans for 1986 are included. (CIAT)